Intersection between modern technologies and halal tourism: exploring the role of digital innovation in enhancing Muslim travellers’ experience - Azam, Md Siddique E; Muflih, Betania Kartika; Al Haq, M Ashraf (Penerbit USIM, 2024)
The rapid pace of digital innovation has significantly impacted various sectors, including tourism. The convergence of halal tourism and digital innovation offers unprecedented possibilities. However, how the fusion between modern technologies and halal tourism can enhance Muslim travellers’ experiences is still not clear. It is crucial to understand the dynamics of amplification through digital avenues, focusing on convenience, accessibility, and cultural enrichment. Simultaneously, the multifaceted ramifications of digital mechanisms and platforms on Muslim travellers’ journeys are poorly understood. Hence, the current study aims to understand Muslim travellers’ preferences and expectations regarding digital innovations in halal tourism. Moreover, it also aims to gain a holistic understanding of their experiences with digital tools in the industry. To achieve the objectives, the study adopts the methodology of reviewing existing literature from various sources. The study provides useful insights into digital innovations. For example, halal-conscious travellers can find comprehensive information on digital platforms; Halal food delivery apps make halal food easy to get. In addition, Muslim travellers can better connect with their destinations through virtual tours of historical landmarks and Indigenous customs using Augmented Reality (AR). At the same time, halal-conscious travellers benefit from an intricate web of experiences, recommendations, and insights woven through online forums, social media groups, and travel blogs. Hence, this study is significant in highlighting the connection between halal tourism and the digital resurgence and the transformative power of technology in enhancing Muslim travellers’ experience. Practical insights for stakeholders in the overlapping fields of halal tourism and technology are explored, including the effects of digital enablers on accessibility, cultural engagement, and community nexus. Furthermore, the findings encourage the development of strategies to cater to the evolving aspirations of travellers seeking Muslim-friendly products and services in the digital era.